Historical dynamics of Batrachochytrium dendrobatidis in Amazonia. Issue 10 (9th December 2015) - Becker, C. Guilherme; Rodriguez, David; Lambertini, Carolina; Toledo, L. Felipe; Haddad, Célio F. B.
Abstract : The Amazon forest is known for its astonishing amphibian diversity, yet the potential distribution and underlying impacts of the most important amphibian pathogen is unknown for most of Amazonia. In this retrospective survey of preserved Leptodactylus frogs, collected over a 119 yr period, we used quantitative PCR to detect the fungal pathogen Batrachochytrium dendrobatidis ( Bd ) and performed spatial scan analyses to identify spatiotemporal clusters of Bd . We also quantified the potential effect of environmental factors on the likelihood of Bd occurrence and generated an updated suitability map for Bd in the Amazon that included our retrospective sampling. We detected Bd in lowland Amazon as early as 1935, in the state of Pará, Brazil, and we found low prevalence (∼ 3.8%) over time. We identified two statistically significant spatiotemporal clusters of Bd : a recent and narrow cluster in the Amazon River delta and a spatiotemporally broad cluster in the southern edge of Amazon and Brazilian savanna. Furthermore, we found an increase in Bd ‐positive samples in the southwestern Amazon after the 1990s, coinciding with reported amphibian declines in neighboring high elevation sites on Andean slopes of Peru. Spatial regressions indicated that higher human interference, higher precipitation, and lower temperatures were significant predictors of Bd occurrence. Environmental niche modeling predicted some narrow areas of suitable climates along the Amazon's periphery and generally low climatic suitability for Bd in the central Amazon; although, we found clusters of Bd ‐positive samples with unexpectedly high infection loads in areas of predicted low suitability. Our study indicates that accelerated human development may put Amazonian amphibians at risk from Bd introductions, and it highlights the potential need to monitor Bd dynamics near Amazonian port cities.